Pendampingan Sulih Teks Bahasa Inggris pada Konten Video Pegiat Konservasi Ikan di Kabupaten Blitar - Yohana, Elva; Akmal, Syerian Alfariel Mumtazha (JURNAL ABDIMAS DOSMA (JAD), 2024)
The Community Service Program aims to provide assistance to Fajar Bengawan Community Group in providing English subtitles to video narratives about Badher Bank fish conservation as a form of effort to preserve and promote conservation tourism areas to the wider community and the international world through domestic and foreign tourist visits. Badher Bank is a Badher fish conservation area located in Tawangrejo Village, Binangun District, Blitar, East Java. Through the text dubbing assistance program on video content about conservation areas, hoped it can be a promotional media for Tawangrejo Village, Binangun District, Blitar to introduce natural tourism areas to the surrounding community, the wider community to foreign countries. The output of this service is a video with English narration text added to text subtitle.